Applying the Theory of Reasoned Action on the promotion of behaviors related to physical activity in chronic back pain patients - Mohammad Hossein Delshad; Alireza Hidarnia; Fatemeh Pourhaji (Acta Scientiarum. Health Sciences, 2023)
Patient's health with cLBP have a unique place in health policy. This study aimed to evaluate the effect of an educational program based on the TRA on promoting PA - related behavior. The (Reasoned Action theory-based back care) RAT-BAC was a Health Service Center-based RCT comparing the effectiveness of TRA construct. A total of 80 patients who referred to the SBUMS in Tehran, Iran were randomized to a TRA-based intervention group (n=40) and control group (n=40). cLBP completed a self-reported questionnaire at follow-ups; a check list was also used to evaluate the Range of motion of the lumbar spine test skills (LSTS) with modified Schober. The effects investigated the usage of repeated measure analysis Test and analyzed using SPSS 21. There was a significant interaction among the factors “group” and “test time” (p < 0.001), totally, 77 cLBP patients with mean age of (41.04±4.23) in intervention (n=40) and control n=37 an age of (39.03±3.48) in the control group were assessed. At baseline, both groups were identified concerning the TRA constructs (p > 0.05).  Following the intervention, there was a significant difference in the course of 3, 6- month follow up (p<0.001).  The mean score of PA behavior (8.38±1.05) was significantly better than the control group (3.23±1.04) (p<0.001). The pain severity (3.75±2.24) was significantly less than the control group (4.28±3.02) (p<0.001). The LSTS reduced within the intervention group (p <0.05). It demonstrated promise in improving PA-related behavior in Patients with cLBP, using a range of specific change educational strategies.